L’Asie du Sud-Est : un ensemble d’États-nations résilients - Michel Bruneau (Bulletin de l’Association de Géographes Français)
The current 11 states of Southeast Asia have sought to conform to the nation state model of Western Europe since their independence gained after the Second World War. If the current definition of their borders dates back to the colonial period of the first half of the 20th century, the States of the Indochinese Peninsula and Indonesia are inherited from the Mandala-States of the pre-colonial period, clearly distinguished from the other States of the ’Archipelago where city-states and sultanates have long dominated along maritime routes, and where the borders resulting from colonization are at the origin of the Philippines, Malaysia or East Timor. The territorial disputes with ethnic minorities and the logic of fragmentation have not succeeded in seriously undermining these nation-states whose resilience is reinforced by their authoritarian and centralized regimes, and by ASEAN which intends to preserve their sovereignty.